Caprine demineralized bone matrix (DBMc) in the repair of non-critical bone defects in rabbit tibias. A new bone xenograft - Santos, Felipe Rocha Dos; Minto, Bruno Watanabe [UNESP]; Silva, Sidney Wendell Goiana da; Coelho, Livia de Paula; Rossignoli, Pedro Paulo; Costa Junior, Jose Sergio; Taba Junior, Mario; Dias, Luis Gustavo Gosuen Gonçalves [UNESP] (FapUNIFESP (SciELO), 2020)
PURPOSE: To evaluate the use of demineralized bone matrix of caprine origin in experimental bone defects of the tibia in New Zealand rabbits. METHODS: Fragments of the tibia diaphysis were collected aseptically from clinically healthy goats. The bones were sectioned into 1 cm fragments and stored at -20°C for subsequent hydrochloric acid (HCL) demineralization. A 70 mg portion of DBMc was used to fill the experimental bone defects. Twenty-four female adult New Zealand rabbits were divided into 2 groups: the MG (matrix group, left tibia) and CG (control group, right tibia). Additionally, they were separated into 4 groups with 6 animals, according to the period of analysis (15, 30, 60 and 90 days postoperatively). Using microCT, volumetric parameters were evaluated: bone volume, relationship between bone volume and total volume, bone surface area, relationship between bone surface area and total volume, number of trabeculae, trabecular thickness and trabecular separation. RESULTS: There was a statistically significant difference (P<0.05) between groups considering bone volume (BV) and bone:total volume (BV/TV), on 15, 30 and 90 days postoperatively. Control group showed a statistically significant superiority (P < 0.05) considering the mean of the variables bone surface (BS), number of trabeculae (Tb.N) and between bone surface and total volume (BS/TV) at 15 and 90 days. CONCLUSIONS: Caprine demineralized bone matrix was safe and tolerable. No signs of material rejection were seen macroscopically. It is an alternative for the treatment of bone defects when autologous graft is not available or in insufficient quantities.